Use of indirect computed tomography lymphangiography to determine metastatic status of sentinel lymph nodes in dogs with a pre‐operative diagnosis of melanoma or mast cell tumour. (30th March 2020) - Grimes, Janet A.; Secrest, Scott A.; Wallace, Mandy L.; Laver, Travis; Schmiedt, Chad W.
Abstract: Canine melanomas and mast cell tumours (MCTs) frequently metastasize to lymph nodes, worsening prognosis compared with dogs without metastasis. Sentinel lymph node (SLN) evaluation is more specific than evaluation of the lymph node closest to the tumour, which may not be the draining lymph node. Computed tomography lymphangiography (CTL) allows for SLN identification and one study of canine mammary tumours found that CTL was able to assist in determination of the metastatic status of inguinal SLNs prior to extirpation and histopathology. The objective of the present study was to evaluate CTL for use in determining metastasis to the SLN in dogs with a pre‐operative diagnosis of melanoma or MCT in various locations by correlating CTL findings with histopathology. The hypothesis was that CTL would not be able to determine the metastatic status of lymph nodes, based on author experience. Dogs were prospectively enrolled and underwent CTL and subsequent SLN extirpation. Histopathology results for the primary tumour, SLN, and additional extirpated lymph nodes were recorded. Fifteen dogs were enrolled and 21 SLN were evaluated. The SLN enhancement pattern (heterogeneous, homogenous or peripheral) was not associated with metastasis, nor was the attenuation value at 1 minute, 5 minutes, or the change in attenuation value. No correlation was found between CTL findings and metastatic status of SLNs. Based on these results, CTL alone cannot be used to diagnose SLN metastasis. Extirpation of the SLN with histopathology is recommended to diagnose lymph node metastasis in dogs with melanoma and MCT.